2014
DOI: 10.1371/journal.pone.0087538
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Derangements Are Associated with Mortality in Critically Ill Adult Patients

Abstract: ObjectiveTo identify metabolomic biomarkers predictive of Intensive Care Unit (ICU) mortality in adults.RationaleComprehensive metabolomic profiling of plasma at ICU admission to identify biomarkers associated with mortality has recently become feasible.MethodsWe performed metabolomic profiling of plasma from 90 ICU subjects enrolled in the BWH Registry of Critical Illness (RoCI). We tested individual metabolites and a Bayesian Network of metabolites for association with 28-day mortality, using logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 28 publications
8
138
1
1
Order By: Relevance
“…The Registry of Critical Illness (RoCI) is approved by the Partners Human Research Committee under IRB protocol 2008-P-000495 (14,15).…”
Section: Human Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Registry of Critical Illness (RoCI) is approved by the Partners Human Research Committee under IRB protocol 2008-P-000495 (14,15).…”
Section: Human Subjectsmentioning
confidence: 99%
“…We next tested the four-metabolite training model on the RoCI and CAPSOD clinical cohorts, which had similar metabolomic measurements (8,15). Noninfected SIRS and sepsis differentiation of the CAPSOD and RoCI cohorts has been described in detail (8,(11)(12)(13)15). Sepsis included all patients regardless of final outcome (sepsis, severe sepsis, septic shock, and sepsis nonsurvivors).…”
Section: Identification Of Sepsis Using Metabolomic Differences In Lomentioning
confidence: 99%
“…Although inflammatory responses are important for host defense against invading microbes, excessive inflammation in sepsis can cause severe cell and tissue damage and organ dysfunction, leading to death (2). Our recent studies suggest that altered plasma metabolic profiles may reflect disease severity and predict mortality in critical illnesses such as sepsis (3,4). Furthermore, we have shown that the plasma levels of proinflammatory cytokines (e.g., IL-18) and circulating mitochondrial injury markers, such as mitochondrial DNA, increase in critical illness and are predictive of mortality (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Later, the relationship was also found between p-HPhLA and 28-day mortality in a large study from Roger et al, after analysis of metabolic proiling of plasma samples from 90 ICU subjects [21].…”
Section: Sepsismentioning
confidence: 82%